Effecting Change in Teachers' Epistemological and Pedagogical Beliefs about Vocabulary Learning and Teaching: The Role of Dialogic Reflection. (February 2022) - Chung, Edsoulla
Despite its significance, the relationship between changes in teachers' beliefs regarding specific aspects of language learning and teaching, and the developmental processes of such beliefs in relation to teacher reflection has remained under-researched. Accordingly, this paper reports the results of a case study that examined how two English language teachers who engaged in dialogic reflection on vocabulary learning and teaching experienced changes in their beliefs. Data collected from in-depth semi-structured interviews, teachers' professional dialogues and reflective journals confirm the role of dialogic reflection in facilitating professional learning; reveal the diverse development processes of teachers' epistemological and pedagogical beliefs; and highlight the complicated relationship between knowledge enhancement and belief change. Based on insights gleaned from the study, this paper provides practical suggestions for teacher development and directions for further research.